Larangan Perkawinan pada Hari Geblak : Nilai Adat dan Kearifan Lokal - janeko, Janeko; Sutopo, Sutopo (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
The prohibition on marriage on Geblak Day in Tenggulun Village, Solokuro District, Lamongan Regency, is a tradition still observed by the community today. This study aims to understand the meaning, background, and customary values underlying this prohibition, and how the local wisdom of the Tenggulun Village community maintains tradition amidst modernization. This study employed an ethnographic approach. Data were obtained through observation, interviews, and documentation. Narrative analysis was used for analysis. The results indicate that the prohibition on marriage on Geblak Day serves an important function as a cultural control mechanism, preserving ancestral values, and shaping community identity. The local wisdom underlying this tradition reflects harmony between human and spiritual values.